Ageing Effects of Na-Alginate/PEO Spinning Solution on Electrospinnability and Morphology of Nanofibres - Mohammad Forhad Hossain; Mustafijur Rahman; Md. Golam Nur (European Scientific Journal, ESJ, 2017)
Poly(ethylene oxide) (PEO) loaded alginate nano-fibres were produced by electrospinning of the 4 % (w/w) of 70:30 Na-alginate/PEO spinning solution. In this research, the effects of solution viscosity and storage time of the spinning solution on fibre diameter and morphology were studied. Results show that the viscosity of the spinning solution was 2284 cP at the age of day 1, which was dropped slowly and reached at 2184 cP until day 5. However, the viscosity sharply decreased after 5 days of storing and the mean diameter of the fibres remain similar until 20 days though the uniformity of the fibre diameters decreased significantly. At day 40, the viscosity of the spinning solution dropped 48 cP which yields beads-onstring fibres. The solutions of 5 days and 10 days old produced smooth and uniform nanofibres having mean diameter of 133 nm and 132 nm, respectively. They also produced stable electrospinning fibre jet compared to other solutions. Overall, the results revel that the electrospinnability of Naalginate/PEO spinning solution remain suitable until 10 days of storing time.